Negative-electrode-free lithium secondary battery with amorphous metal alloy coating, lithium metal secondary battery, lithium secondary battery and all-solid-state secondary battery
By coating Zr-based or Ti-based amorphous metal alloys on the interface between Cu current collector and electrolyte of the negative electrode-free lithium metal battery, the problem of Coulomb efficiency reduction caused by the solid-electrolyte interface and dead lithium generation is solved, and the cycling performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202280101657.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-07
- Filing Date
- 2022-11-22
- Publication Date
- 2025-06-13
AI Technical Summary
In negative electrode-free lithium metal batteries, the generation of solid-electrolyte interfaces and dead lithium leads to a decrease in Coulomb efficiency, affecting the cycling performance of the battery.
The interface in which the Cu current collector is in contact with the electrolyte is coated with a Zr- or Ti-based amorphous metal alloy to suppress the formation of solid-electrolyte interface and dead lithium.
By coating amorphous metal alloys, the Coulomb efficiency and cycling performance of negative electrode-free lithium secondary batteries are significantly improved, and the solid-electrolyte interface and the generation of dead lithium are reduced.
Smart Images

Figure CN120153511A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an anode-free lithium secondary battery, a lithium metal secondary battery, a lithium secondary battery, and an all-solid-state secondary battery having an amorphous metal alloy coating. More specifically, the present invention relates to an anode-free lithium secondary battery, a lithium metal secondary battery, a lithium secondary battery, and an all-solid-state secondary battery having an amorphous metal alloy coating, which can suppress the formation of a solid-electrolyte interface and dead lithium generated on the surface of a current collector by coating a Zr-based amorphous metal alloy or a Ti-based amorphous metal alloy on the interface where the Cu current collector contacts the electrolyte. Background Art
[0002] High energy density is one of the important factors for achieving an electric vehicle driving range equivalent to that of an internal combustion engine vehicle and extending the operating time of electronic devices. To achieve high energy density, various attempts have been made to achieve higher specific capacity and smaller volume or lighter battery weight by changing the cell structure of lithium-ion batteries. The lithium metal anode-free battery is considered a promising cell structure for increasing the energy density of lithium-ion batteries. In the lithium metal anode-free battery, there is no active material for the anode such as graphite, so the weight, volume, and cost of the battery can be reduced compared to conventional lithium-ion batteries. However, the components of the anode active material cause a decrease in Coulombic efficiency. The low Coulombic efficiency is the main drawback for the commercialization of lithium metal anode-free batteries, and various attempts have been made to overcome this drawback. The main reason for the low Coulombic efficiency is the excessive consumption of lithium and electrolyte due to the formation of an unstable solid-electrolyte interface (SEI) and dead lithium. The unstable solid-electrolyte interface and dead lithium lead to non-uniform lithium deposition or lithium dendrites on the current collector during the charging process, and this is the result of non-uniform current density on the current collector (CC). The non-uniform surface condition of the current collector and the inherent lithiophobicity of copper (Cu) accelerate the non-uniform deposition of lithium. The sub-millimeter roughness of bare Cu induced in the foil manufacturing process results in non-uniform lithium deposition. In addition, defects such as grain boundaries and impurities, and nano-scale roughness based on the change in the crystal orientation of particles within the current collector also induce non-uniform current density, leading to non-uniform lithium deposition. Based on various surface conditions, the lithiophobicity of Cu causes non-uniform lithium deposition. Based on the solid solution and compound formation characteristics, Cu is known as a relatively lithiophobic material. It has been reported that elements showing solubility in lithium and elements forming compounds with lithium such as gold (Au) and silver (Ag) have lithiophilicity. In contrast, since Cu does not show solubility in lithium or alloying phenomenon between metals with lithium, it shows lithiophobic behavior. In the initial stage of lithium deposition, lithium atomic nuclei are formed in the protruding surface area where the current density is higher than the surrounding area. Then, due to lithiophobicity, lithium ions tend to deposit on the pre-deposited lithium rather than on the surface of the bare Cu current collector. This results in a non-uniform upper end face of the deposited lithium and the growth of lithium dendrites.
[0003] The presence of deposited lithium with a wavy upper surface increases the interfacial area between the electrolyte and the deposited lithium and accelerates the formation of the solid-electrolyte interface layer, thus reducing the Coulombic efficiency. The solid-electrolyte interface layer forms at the interface between the deposited lithium metal and the electrolyte. During cycling, as lithium ions are repeatedly deposited / desorbed on the current collector, the shape of the deposited lithium changes. This results in the formation of cracks in the solid-electrolyte interface layer, and the deposited lithium continues to be exposed to the electrolyte. The solid-electrolyte interface continues to form during the cycling process that consumes lithium and the electrolyte. In addition to the lithium consumption due to the formation of the solid-electrolyte interface, the formation of lithium fragments also results in a reduction in the Coulombic efficiency. Since lithium fragments are lithium dendrites separated from the deposited lithium, they are electrochemically inactive. Lithium dendrites tend to form at positions with a higher local current density over time according to Sand time. During the lithium desorption process, uneven dissolution forms lithium fragments, which are called "dead lithium". Another drawback of the formation of lithium dendrites is the cause of short circuits. If the lithium dendrites continue to grow, they will eventually contact the positive electrode, resulting in a short circuit.
[0004] Many attempts have been made to improve the Coulombic efficiency of the lithium metal battery without a negative electrode. Among them, the evaluation of coating the current collector with various thin films has been carried out. Regarding the coating on the current collector, mainly three types of materials, namely carbon-based, organic-based, and metal-based, have been studied. Among them, the advantage of the metal-based material is that it has excellent electrical conductivity and strong adhesion to the Cu current collector. The metal coating acts as a protective layer to prevent the corrosion of the current collector and severe volume changes during cycling. As the coating on the current collector, various metals have been investigated, and it has been demonstrated that lithiophilic metal layers such as silver (Ag), gold (Au), and tin (Sn) promote uniform lithium deposition. During the lithium deposition process, the coated metal dissolves in the deposited lithium to form a solid solution layer, thus effectively reducing the nucleation overpotential. As the coating, not only lithiophilic metals but also lithium-phobic compounds have been used. The chemical reaction between lithium and the nanostructured lithium-phobic material results in a transformation from lithium-phobic to lithiophilic, which improves the electrochemical performance. Summary of the Invention
[0005] Problems to be Solved by the Invention
[0006] To solve the problems described above, the present invention provides a lithium metal secondary battery without a negative electrode, a lithium metal secondary battery, a lithium secondary battery, and an all-solid-state secondary battery having a Zr-based amorphous metal alloy and a Ti-based amorphous metal alloy coating, wherein the formation of the solid-electrolyte interface and the generation of dead lithium (reducing the Coulombic efficiency of the lithium metal battery without a negative electrode) formed at the interface between the Cu current collector and the electrolyte can be suppressed.
[0007] Technical Solution
[0008] To achieve the above object, the non-aqueous lithium secondary battery having an amorphous metal alloy coating according to the first embodiment of the present invention is characterized in that it includes: a positive electrode; a current collector disposed opposite to the positive electrode and made of a copper foil; an electrolyte located between the positive electrode and the current collector; and a separator separating the positive electrode and the current collector; an amorphous metal alloy is coated on the interface where the current collector contacts the electrolyte.
[0009] In addition, the lithium metal secondary battery having an amorphous metal alloy coating according to the second embodiment of the present invention is characterized in that it includes: a positive electrode; a lithium metal negative electrode disposed opposite to the positive electrode; an electrolyte located between the positive electrode and the lithium metal negative electrode; and a separator separating the positive electrode and the lithium metal negative electrode; an amorphous metal alloy is coated on the surface of the lithium metal negative electrode.
[0010] In addition, the lithium secondary battery having an amorphous metal alloy coating according to the third embodiment of the present invention is characterized in that it includes: a positive electrode; a lithium metal negative electrode disposed opposite to the positive electrode; a current collector contacting the lithium metal negative electrode and located in the opposite direction to the positive electrode and made of a copper foil; an electrolyte located between the positive electrode and the lithium metal negative electrode; and a separator separating the positive electrode and the lithium metal negative electrode; an amorphous metal alloy is coated on the surface of the lithium metal negative electrode.
[0011] In addition, the all-solid-state secondary battery having an amorphous metal alloy coating according to the fourth embodiment of the present invention is characterized in that it includes: a positive electrode; a negative electrode disposed opposite to the positive electrode; and a solid electrolyte filled between the positive electrode and the negative electrode; an amorphous metal alloy layer exists at the interface between the solid electrolyte and the negative electrode.
[0012] In addition, the current collector according to the fifth embodiment of the present invention is characterized in that it is a negative current collector with an amorphous metal alloy coated on its surface.
[0013] In addition, the manufacturing method of the non-aqueous lithium secondary battery having an amorphous metal alloy coating according to the sixth embodiment of the present invention is characterized in that the manufacturing method of the non-aqueous lithium secondary battery includes: a positive electrode; a current collector disposed opposite to the positive electrode and made of a copper foil; an electrolyte located between the positive electrode and the current collector; and a separator separating the positive electrode and the current collector; the current collector is formed by magnetron sputtering an amorphous metal alloy on a copper thin film.
[0014] In the first to sixth embodiments, the amorphous metal alloy is characterized in that it is selected from any one or a mixture of two or more of lanthanum-based (La), cerium-based (Ce), praseodymium-based (Pr), promethium-based (Pm), samarium-based (Sm), lutetium-based (Lu), yttrium-based (Y), neodymium-based (Nd), gadolinium-based (Gd), terbium-based (Tb), dysprosium-based (Dy), holmium-based (Ho), erbium-based (Er), thulium-based (Tm), thorium-based (Th), calcium-based (Ca), scandium-based (Sc), barium-based (Ba), beryllium-based (Be), bismuth-based (Bi), germanium-based (Ge), lead-based (Pb), ytterbium-based (Yb), strontium-based (Sr), europium-based (Eu), zirconium-based (Zr), thallium-based (Tl), lithium-based (Li), hafnium-based (Hf), magnesium-based (Mg), phosphorus-based (P), arsenic-based (As), palladium-based (Pd), gold-based (Au), plutonium-based (Pu), gallium-based (Ga), germanium-based (Ge), aluminum-based (Al), copper-based (Cu), zinc-based (Zn), antimony-based (Sb), silicon-based (Si), tin-based (Sn), titanium-based (Ti), cadmium-based (Cd), indium-based (In), platinum-based (Pt), and mercury-based (Hg) amorphous metal alloys.
[0015] In the first to sixth embodiments, the amorphous metal alloy is characterized in that it is a Zr-based amorphous metal alloy.
[0016] In the first to sixth embodiments, the Zr-based amorphous metal alloy is characterized in that it is Zr x Cu y Ni z Al w compound, wherein the range of x is 35 to 70, the range of y is 20 to 50, the range of z is 7 to 15, and the range of w is 3 to 5. More preferably, the range of x is 40 to 50, the range of y is 25 to 35, the range of z is 10 to 13, and the range of w is 4 to 5.
[0017] In the first to sixth embodiments, the amorphous metal alloy is a Ti-based amorphous metal alloy, and the Ti-based amorphous metal alloy may include one of Ti-Cu, Ti-Cu-Al, Ti-Cu-Nb, Ti-Cu-Ni, Ti-Cu-Ni-Sn, Ti-Cu-Ni-Sn-Zr, Ti-Cu-Ni-Zr, Ti-Cu-Ni-Sn-Zr, and Ti-Zr-Si amorphous metal alloys.
[0018] In the first to sixth embodiments, the Ti-based amorphous metal alloy is characterized in that it is Ti a Zr b Si cThe compound has a in the range of 45 to 85, b in the range of 20 to 50, and c in the range of 5 to 10. More preferably, a is in the range of 60 to 70, b is in the range of 22 to 28, and c is in the range of 8 to 10.
[0019] In the first to sixth embodiments, the coating thickness of the amorphous metal alloy is characterized in that it is 8 nm to 500 nm, preferably 8 nm to 200 nm, more preferably 8 nm to 24 nm, and most preferably 8 nm to 16 nm.
[0020] The amorphous metal alloy can use metallic glass.
[0021] The method for preparing a lithium-free secondary battery having an amorphous metal alloy coating according to the present invention includes: a preparation step of preparing a lithium foil; and a deposition step of depositing an amorphous metal alloy on the lithium foil by magnetron sputtering.
[0022] Among them, in an inert gas atmosphere, sputtering based on magnetron sputtering can be carried out at 10 -3 to 10 -7 Torr for 30 seconds to 3 minutes.
[0023] Advantages of the Invention
[0024] As described above, the present invention has the following effects: inhibiting the formation of solid-electrolyte interface and dead lithium in the half-cell and full-cell of the lithium-free secondary battery, thereby exhibiting excellent cycling performance. Description of the Drawings
[0025] Figure 1 Part (a) of shows the Coulombic efficiency of a half-cell in which a Zr-MG thin film with a thickness of 8 nm, 12 nm, 16 nm, 24 nm, and 32 nm is coated on a current collector. Figure 1 Part (b) of shows the voltage curve of the first-cycle specimen of a half-cell in which a Zr-MG thin film with a thickness of 8 nm, 12 nm, 16 nm, 24 nm, and 32 nm is coated on a current collector. Figure 1 Part (c) of shows the voltage curve of a half-cell in which a Zr-MG thin film with a thickness of 8 nm, 12 nm, 16 nm, 24 nm, and 32 nm is coated on a current collector. Figure 1 Part (d) of compares the Coulombic efficiency of a half-cell having a current collector coated with 12 nm of Zr-MG when not heated or heated at a temperature of 100 °C for 10 minutes.
[0026] Figure 2 Part (a) of shows half-cells having a current collector without 12-MG coating and a current collector with 12-MG coating at 0.1 mAh cm -2 and 0.5 mAh cm-2 Overpotential under the conditions of Figure 2 Part (b) of is the SEM image of lithium deposits on the current collector coated with 12-MG after one hour under the condition of 0.1 mAh cm -2 The SEM image of lithium deposits after one hour under the conditions of Figure 2 Part (c) of is the SEM image of lithium deposits on the current collector coated with 12-MG after 5 hours under the condition of 0.5 mAh cm -2 The SEM image of lithium deposits after 5 hours under the conditions of Figure 2 Part (d) of is the SEM image of lithium deposits on the current collector coated with 12-MG Figure 2 Part (e) of is the SEM image of lithium deposits on the current collector without 12-MG coating after one hour under the condition of 0.1 mAh cm -2 The SEM image of lithium deposits after one hour under the conditions of Figure 2 Part (f) of is the digital image of lithium deposits on the current collector without 12-MG coating after 5 hours under the condition of 0.5 mAh cm -2 The digital image of lithium deposits after 5 hours under the conditions of Figure 2 Part (g) of is the digital image of lithium deposits on the current collector without 12-MG coating
[0027] Figure 3 Part (a) of is the electrochemical impedance spectroscopy (EIS) measurement, which is the Nyquist plot of bare Cu and the current collector coated with 12-MG after the first cycle discharge after pre-cycling Figure 3 Part (b) of is the Nyquist plot of bare Cu and the current collector coated with 12-MG after the 100th discharge cycle
[0028] Figure 4 Part (a) of shows the SEM image (magnification X100000) of lithium deposits on bare Cu after one hour under the condition of 0.1 mAh cm -2 The SEM image (magnification X100000) of lithium deposits after one hour under the conditions of Figure 4 Part (b) of shows the SEM image (magnification X100000) of lithium deposits on the current collector coated with 12-MG after one hour under the condition of 0.1 mAh cm -2 The SEM image (magnification X100000) of lithium deposits after one hour under the conditions of Figure 4 Part (c) of is the upper surface image of bare Cu without lithium deposits Figure 4 Part (d) of is the upper surface image of the current collector coated with 12-MG without lithium deposits
[0029] Figure 5 Part (a) of shows the XPS curve of Zr on the upper surface of the current collector coated with deposited 12-MG under the cycling conditions of 0.5, 1.0, and 6.5 Figure 5 Part (b) of is the TEM photo of the deposited 12-MG Figure 5Part (c) is the TEM photograph of 12-MG after 1 cycle.
[0030] Figure 6 Shows the cycling performance at 0.2C of a full cell assembled with bare Cu as the counter electrode, current collectors coated with 12-MG and 16-MG, and LiFePO 4 Part (a) is the SEM top surface image of the deposited lithium on the current collector coated with 12-MG after the first deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm
[0031] Figure 7 Part (b) is the SEM top surface image of the deposited lithium on the bare Cu current collector after the first deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (c) is the SEM top surface image of the deposited lithium on the current collector coated with 12-MG after the 100th deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (d) is the SEM top surface image of the deposited lithium on the bare Cu current collector after the 100th deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (e) is the SEM cross-sectional image of the deposited lithium on the current collector coated with 12-MG after the first deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (f) is the SEM cross-sectional image of the deposited lithium on the bare Cu current collector after the first deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (g) is the SEM cross-sectional image of the deposited lithium on the current collector coated with 12-MG after the 100th deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (h) is the SEM cross-sectional image of the deposited lithium on the bare Cu current collector after the 100th deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 ) Figure 7 Part (i) is the SEM cross-sectional image of the deposited lithium on the bare Cu current collector after the 100th deposition at a rate of 0.2C in a full cell with an LFP positive electrode (1 mAh / cm 2 )
[0032] Figure 8 Shows at 1.5 mA / cm 2Under the condition that the electrolyte is 1 M LiTFSl + 2 wt% LiNO in DOL / DME 3 , the discharge capacity of the cycle of bare lithium in a full cell with a charge / discharge rate of 1.0 C.
[0033] Figure 9 Part (a) of shows 1.5 mA / cm 2 Under the condition that the electrolyte is 1 M LiTFSl + 2 wt% LiNO in DOL / DME 3 , the discharge capacity of the cycle of the negative electrode coated with a Zr-based amorphous metal alloy with a thickness of 12 nm and 200 nm in a full cell with a charge / discharge rate of 1.0 C, Figure 9 Part (b) of shows the relationship between the cycles and peak points of 5 Zr-based amorphous metal alloys.
[0034] Figure 10 Part (a) of shows that at 1.5 mA / cm 2 Under the condition that the electrolyte is 1 M LiTFSl + 2 wt% LiNO in DOL / DME 3 , the discharge capacity of the cycle of the negative electrode coated with a Ti-based amorphous metal alloy with a thickness of 12 nm in a full cell with a charge / discharge rate of 1.0 C, Figure 10 Part (b) of shows the relationship between the cycles and peak points of 2 Ti-based amorphous metal alloys. Detailed Description of the Invention
[0035] The present invention can be modified in various ways and has multiple embodiments. Specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the present invention to specific embodiments, but should be understood to include all modifications, equivalents, and substitutes that fall within the spirit and technical scope of the present invention. In the process of describing each drawing, similar reference numerals are used for similar components.
[0036] Terms such as "first", "second", "A", and "B" can be used to describe various components, and the components should not be limited by these terms. These terms are only used for the purpose of distinguishing one component from other components.
[0037] For example, without departing from the scope of the claims of the present invention, the first component can be named the second component, and similarly, the second component can also be named the first component. The term "and / or" includes combinations of multiple related recited items or any item among multiple related recited items.
[0038] When referring to a certain component being "connected" or "coupled" to other components, it should be understood that the other components can be directly connected or coupled, or there can be other components in between. Conversely, when referring to a certain component being "directly connected" or "directly coupled" to other components, it should be understood that there are no other components in between.
[0039] The terms used in the present invention are only used to describe specific embodiments and are not intended to limit the present invention. Unless otherwise clearly stated herein, singular expressions include plural expressions. In the present invention, terms such as "comprising" or "having" are used to describe the existence of features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should not be construed as precluding the existence or additional possibility of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0040] Unless otherwise defined, all terms (including technical terms or scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention pertains. Terms that are the same as those defined in a common dictionary should be interpreted as having a meaning consistent with the context of the relevant technology, and should not be interpreted as having an idealized or overly formalized meaning unless clearly defined otherwise in the present invention.
[0041] In the present invention, Zr is used as the coating of the Cu current collector 54 Cu 31 Ni 11 Al 4, namely Zr-based amorphous metallic alloy, which greatly improves the electrochemical performance of the lithium metal battery without a cathode. A Zr-based amorphous metallic alloy thin film with a thickness of 12 nm was deposited by a magnetron sputtering process. The amorphous metallic alloy is an amorphous metallic alloy that exhibits glassy behavior (such as glass transition) during heating. Their amorphous structure provides many advantages in improving the electrochemical characteristics of the current collector. First, since amorphous materials without long-range order do not have defects such as grain boundaries, potential, and stacking defects, a uniform environment for lithium deposition is provided. This removes the atomic-level roughness, crystal orientation, and compositional diversity. In the zirconium metallic glass (Zr-Metallic Glass, Zr-MG) thin film, short-range or medium-range order results in chemical and physical uniformity on the surface, and this uniformity causes uniform deposition of lithium during the charging process. Second, the amorphous structure has a disordered phase with many atomic vacancies. Compared with crystalline alloys, since the amorphous structure exhibits higher elasticity, more lithium ion insertion sites are provided. More lithium ion insertion sites provide a lithiophilic environment, and the inserted lithium converts Zr-MG into a lithiophilic phase. Since the main component Zr in Zr-MG has insufficient solubility for lithium and does not form an intermetallic with lithium, it is classified as a lithium-phobic element. However, Zr reacts with lithium ions to form a lithiophilic Li 2 ZrO 3 thin film. The lithiophilic Zr-Li phase at the upper end of the Zr-MG thin film induces uniform lithium deposition. Generally, amorphous metallic alloys exhibit excellent mechanical and physical properties such as mechanical strength and elasticity, so they are mainly used as structural materials. The research group of amorphous metallic alloys mainly focuses on the mechanical properties and glass-forming ability of amorphous metallic alloys. It is well known that amorphous metallic alloys have not been regarded as coatings for current collectors so far. The Zr-MG thin film with atomic-level uniformity, the number of atomic vacancies, excellent elasticity, and the formation of a lithiophilic Zr-Li phase results in uniform deposition of lithium on the current collector. The uniform deposition of lithium at the initial stage of deposition ultimately significantly reduces the solid-electrolyte interface impedance (R SEI ) and charge transfer impedance (R ct ).
[0042] [Zr-MG Target Preparation Method]
[0043] To create a high-vacuum environment, before starting the arc furnace equipment, preheat the diffusion pump for about one hour. Put each element of Zr, Cu, Ni, and Al into the main chamber of the arc furnace, and control the vacuum to below 10 -3 Torr through a rotary pump, and then control the vacuum to below 10 -5 Torr through a diffusion pump. When the high-vacuum state is reached, open the gas valve, introduce Ar gas, and then melt the sample by an arc beam to prepare Zr 54 -Cu 31-Ni 11 -Al 4 (at%) sputtering target. The prepared target has a height of 11.72 mm and a diameter of 50.53 mm, which is not suitable for entering the sputtering target holder. Therefore, it is cut into a height of 4.78 mm using a wire cutting machine and then processed through a double-sided polishing operation to adjust the surface height and balance.
[0044] [Electrode preparation method]
[0045] The prepared Zr 54 -Cu 31 -Ni 11 -Al 4 The target is deposited on a clean Cu foil by using a magnetron sputtering system (the reference pressure in the sputtering chamber is below 4×10 -6 Torr). The Cu foil is heated at 373.15 K or not heated (R.T), and in an Ar atmosphere of 5×10 -3 Torr, Zr 54 -Cu 31 -Ni 11 -Al 4 is sputtered at 125 W of DC. The Cu foil coated with Zr 54 -Cu 31 -Ni 11 -Al 4 is placed in the vacuum sputtering chamber until it cools to 300.15 K. To prepare the cell, the current collector coated with Zr 54 -Cu 31 -Ni 11 -Al 4 after the sputtering process is directly moved into the glove box through the gate without being exposed to the air.
[0046] [Cell preparation method]
[0047] The half-cell uses a Zr 54 -Cu 31 -Ni 11 -Al 4 / Cu foil with a diameter cut to 18 mm as the working electrode, and the diameter of the Li metal is cut to 16 mm and used as the counter electrode. The CR2032 button cell model is used in an Ar atmosphere (O 2 <1 ppm, H 2The battery cells were prepared in a glove box with O < 1 ppm. The half-cells were prepared in the following order: outer shell, 18 mm electrode, separator (Celgard 2400), 70 μL of electrolyte (1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME) in a 1:1 ratio containing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), containing 2 wt% lithium nitrate (LiNO 3 ))., 16 mm lithium metal, gasket, wave spring and lid.
[0048] For the full cell, Zr 54 -Cu 31 -Ni 11 -Al 4 / Cu foil was used as the negative electrode, and LiFePO 4 (LFP) with a diameter of 14 mm was used as the positive electrode. The ratio of LFP / carbon black / poly(vinylidene fluoride) was 8:1:1, and the areal capacity of the positive electrode was 1.0 mAh / cm 2 . The battery cells were prepared in a glove box with an Ar atmosphere (O 2 < 1 ppm, H 2 O < 1 ppm). The full cells were prepared in the following order: outer shell, 14 mm LFP, separator (Celgard 2400), 70 μL of electrolyte (1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME) in a 1:1 ratio containing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), containing 2 wt% lithium nitrate (LiNO 3 ))., 16 mm negative electrode, gasket, wave spring and lid.
[0049] [Battery cell performance evaluation]
[0050] The performance of the battery cells was evaluated using a WBCS 3000Le device and was carried out at room temperature after 24 hours of aging. Electrochemical impedance spectroscopy (EIS) for impedance measurement was performed using a Zive SP2 with an amplitude of 5 mV at room temperature (frequency range: 1 MHz to 100 mHz). ZMAN software was used to fit the EIS data.
[0051] The thickness of the coating was optimized by analyzing the Coulomb efficiency of a half-cell equipped with a current collector (coated with Zr-MG thin films of various thicknesses from 8 nm to 32 nm). The amorphous structure and composition of the Zr-MG thin films were confirmed by XRD and SEM EDS. For comparison Figure 1 of part (a), Figure 1 of part (b), and Figure 1 of part (c) of the cell performance per unit thickness, half-cells of 8 nm, 12 nm, 16 nm, 24 nm, and 32 nm were prepared by depositing at a rate of 3.75 s per nm under the condition of 125 WRT (room temperature) (a bare Cu half-cell was also prepared for comparison with bare Cu). Then, charge and discharge were carried out under the conditions of 1.0 mA / cm 2 and 1.0 mAh / cm 2 to evaluate the performance of the electrodes. Figure 1 In part (d), 12 nm and 16 nm showed better Coulomb efficiency, voltage curve, and voltage hysteresis characteristics than other thicknesses. Therefore, only one of the two conditions (16 nm) was used to compare the differences that occurred depending on whether heat treatment was performed. The non-heat-treated electrodes were deposited at a thickness of 16 nm under the condition of R.T, while the heat-treated electrodes were additionally heat-treated for 10 minutes at 373.15 K after sputtering. Then, charge and discharge were carried out under the conditions of 1.0 mA / cm 2 and 1.0 mAh / cm 2 to evaluate the performance of the electrodes. As Figure 1 shown in part (a), compared with the uncoated current collector, the Coulomb efficiency of the current collector with a Zr-MG layer deposited on it increased. Compared with the uncoated or current collectors coated with thinner or thicker Zr-MG thin films, the current collectors coated with Zr-MG thin films with a thickness of 12 nm and 16 nm showed more stable and higher Coulomb efficiency. In the half-cells, the Coulomb efficiencies of the current collectors coated with 12-MG and 16-MG were 97.8% (97.8 ± 0.60%) and 97.5% (97.7 ± 0.60%) respectively in the 100th cycle (see Table 1).
[0052] Table 1
[0053]
[0054] (Unit: %)
[0055] It is confirmed that the narrower the standard deviation of the average Coulomb efficiency, the more stable the cycling performance of the current collectors coated with 12-MG and 16-MG, and it is judged that Zr-MG with a thickness of 8 nm is insufficient to improve the cycling performance. The Zr-MG layer with a thickness greater than 24 nm can reduce the electrochemical performance of the current collector by increasing the internal impedance. In Figure 1 In the first cycle of part (b) of Figure 1 , the corresponding voltage curves of the half-cells also show that the current collectors coated with Zr-MG with a thickness of 12 - 24 nm exhibit higher capacities than others. It can be confirmed that their voltage hysteresis ( Figure 1 part (c) of Figure 1 ) remains at a low hysteresis voltage due to the Zr-MG coating. For Zr-MG with thicknesses of 8 nm and 32 nm, the voltage increases rapidly after 70 cycles. The increase in the hysteresis voltage is closely related to
[0056] The 12-MG coating significantly changes the overpotential measured during the lithium deposition process in the first cycle. The overpotential is a measurable physical parameter related to lithium nucleation and growth in the current collector, and it is obtained from the voltage measured over time under a constant current condition. The overpotential curve shows a deep spike followed by a stabilized region. The overpotential for lithium nucleation in the current collector is the sum of the charge transfer, diffusion, reaction, and crystallization overpotentials. As another method, the electrode polarization during the lithium deposition process on the current collector can be regarded as the sum of two terms. They are the nucleation overpotential (η n ) and the growth overpotential (η p ), where the nucleation overpotential (η n ) is related to the nucleation of lithium clusters at the initial stage of deposition and is observed as a voltage spike, and the growth overpotential (η p)It is used to illustrate the growth of lithium in existing lithium nuclei, and the observed voltage curve is almost flat. The peak voltage of the current collector (Zr-CC) coated with 12-MG is 52 mV, which is 13 mV lower than that of the bare current collector (65 mV). The growth overpotential of Zr-CC measured during the 5-hour deposition process is 13 mV, which is lower than 21 mV of the bare current collector. The nucleation overpotentials, which are the differences between the peak potential and the growth potential of Zr-CC and the bare current collector, are 39 mV and 44 mV respectively. Although the difference is not significant, it can be seen that by depositing an amorphous metal alloy film on the current collector, the overall overpotential is slightly reduced. Compared with the overpotential values, the shapes of the overpotential curves are significantly different. For Zr-CC after the voltage peak appears, the voltage increases rapidly and saturates after 1 hour of deposition. For the bare Cu, the voltage continues to increase for up to 5 hours without reaching a saturation state. This difference should stem from the differences among the four overpotentials between the bare current collector and Zr-CC. Among the four overpotentials, it is expected that the charge transfer, diffusion, and crystallization overpotentials mainly contribute to the differences in the overpotential curves. This is because, regardless of whether the current collector is coated or not, no significant differences are expected in the chemical reactions before and after lithium deposition. At the Li / Cu interface deposited in the nucleation state and the Li / Zr-CC interface deposited, due to the differences in the characteristics of each interface and the differences in the shape of lithium deposition in the growth state, the overpotential differences in charge transfer, diffusion, and crystallization are caused. Through the inference of the overpotential curve, it can be hypothesized that once lithium ions start to deposit on Zr-CC, compared with the bare Cu, nuclei are formed within 1 hour and uniformly cover the current collector. Lithium continues to deposit in the growth state on top of the nuclei. For the bare Cu current collector, during the growth of existing nuclei, nucleation continues, indicating that the nucleation state and the growth state widely overlap.
[0057] In Figure 2 part (a), half-cells were prepared using a current collector coated with Zr MG with a thickness of 12 nm and bare Cu, and charged under the conditions of 0.1 mA / cm 2 and 0.5 mAh / cm 2 to compare the overpotentials. In Figure 2 part (b) and Figure 2 part (e), half-cells were prepared using a current collector coated with Zr MG with a thickness of 12 nm and bare Cu, and after charging for 1 hour under the current density condition of 0.1 mA / cm 2 , the battery cells were disassembled. If necessary, the samples were rinsed with 1,2-dimethoxyethane (DME) to remove residual Li salts. Then, the surface was observed by SEM at a magnification of 500 times. In Figure 2 part (c) and Figure 2 part (f), half-cells were prepared using a current collector coated with Zr MG with a thickness of 12 nm and bare Cu, and at 0.1 mA / cm2 After charging for 5 hours under the current density condition of Figure 2 , the battery cell was disassembled. If necessary, the sample was rinsed with 1,2 - dimethoxyethane (DME) to remove residual Li salts. Then, the surface was observed by SEM at a discharge rate of 500. In Figure 2 , for the (d) part of 2 and the (g) part of Figure 2 , a half - cell was prepared using a current collector coated with 12 nm thick Zr MG and bare Cu, and after charging for 5 hours under the current density condition of 0.1 mA / cm Figure 2 , the battery cell was disassembled and an image of the electrode with lithium deposition was taken. The lithium deposits were analyzed using SEM, and the relationship between the shape of the lithium deposits and the over - potential was observed ( 2 from the (b) part of Figure 2 to the (g) part of Figure 2 ). At the initial stage of lithium deposition (deposited for 1 hour, 0.1 mAh / cm 2 ), lithium deposits on Zr - CC were granular, while lithium deposits on bare Cu were granular and dendritic simultaneously ( Figure 2 in the (b) part of Figure 2 and the (d) part of Figure 2 ). If the number of nuclei of Zr - CC and bare Cu is proportional to one of the particles and dendrites, then the two are similar. This may be because they have comparable nucleation over - potentials. After deposition (0.5 mAh / cm Figure 2 ) for 5 hours, lithium grew uniformly on Zr - CC covering a larger area of the current collector, while in bare Cu, the growth trend of dendrites was obvious. As shown in the (c) part of -2 and the (e) part of Figure 2 , a larger area of the current collector not covered by lithium was left in bare Cu. In the (f) part of
[0058] and the (g) part of Figure 3 , it was visually confirmed that Zr - CC grew uniformly over the entire area, while it was visually confirmed that only about 75% of the area was covered by lithium. This clearly shows that due to the 12 - MG coating, lithium deposits uniformly on the current collector, and it means that the larger the deposition area, the lower the effective current density (mAh / cm Figure 3In part (b), half-cells were prepared using a current collector coated with 12 nm thick ZrMG and bare Cu, and after 100 cycles, impedance was measured by performing EIS. The measurement by electrochemical impedance spectroscopy (EIS) clearly showed that the 12-MG coating significantly reduced the SEI impedance (R SEI ) and charge transfer impedance (R ct ). During the first cycle, the R SEI and R ct of Zr-CC were 38.2 Ω and 58.5 Ω, respectively, which were much lower than 76.5 Ω and 255.9 Ω of the bare current collector. Even after 100 cycles, the impedance of Zr-CC was still lower than that of the bare current collector. After 100 deposition processes, the R SEI and R ct of Zr-CC (21.3, 11.4 Ω) were relatively lower than those of bare Cu (17.8, 146.8 Ω) ( Figure 3 part (b)). Therefore, the 12-MG coating reduced the R SEI and R ct that are required to guide low nucleation and stable overpotential.
[0059] Based on the overpotential of the 12-MG coating, the reduction of R SEI and R ct brought about a difference in the nanoscale morphology of lithium deposits. The current collector regions without lithium particles or dendrites in part (b) of Figure 2 and part (d) of Figure 2 were magnified and observed by SEM, and are shown in Figure 4 . In part (a) of Figure 4 and part (b) of Figure 4 , half-cells were prepared using bare Cu and a current collector coated with 12 nm thick ZrMG, and after charging for 1 hour under a current density condition of 0.1 mA / cm 2 , the battery cells were disassembled. If necessary, the samples were rinsed with 1,2-dimethoxyethane (DME) to remove residual Li salts. Then, the surface was observed by field emission scanning electron microscopy (FE-SEM) at a magnification of 100,000. In part (c) of Figure 4 and part (d) of Figure 4 , the surface of the current collector using bare Cu and a current collector coated with 12 nm thick ZrMG was observed by field emission scanning electron microscopy (Field Emission Scanning ElectronMicroscopy, FE-SEM) at a magnification of 100,000. As Figure 4As shown in part (a), there are multiple particles with a diameter of approximately 200 nm on the bare Cu current collector, and smaller particles (nanoparticles) with a diameter of approximately 20 nm cover the bare current collector. Nucleation occurs at the initial stage of deposition on the bare Cu and is expected to grow to approximately 20 nm within 1 hour. Boundaries and empty regions between the nanoparticles are observed in the bare Cu. For 12-MG, the nanoparticles are tightly bound to each other, as Figure 4 shown in part (b), forming a smooth and almost continuous lithium film. The interfaces or empty regions between the nanoparticles are hardly observable. By comparing the surface conditions of the bare Cu without lithium deposits ( Figure 4 part (c)) with those of Zr-CC ( Figure 4 part (d)), the formation of nanoparticles on the bare Cu and Zr-CC was confirmed. High-magnification morphological studies in SEM confirmed the formation of a lithium thin film at the initial stage of lithium deposition. Fine particles and lithium dendrites are formed on the lithium thin film. The almost continuous lithium film formed on the Zr-CC supports the rapid reduction of the overpotential after the voltage spike (refer to Figure 2 part (a)).
[0060] Conversely, the discontinuous lithium film on the bare current collector allows lithium ions to be deposited on both the bare current collector and the Li film, that is, in the overlapping nucleation state (formation of nanoparticles) and the growth state (formation of nanoparticles and lithium dendrites). Thus, as Figure 2 shown in part (a), the overpotential of the bare Cu continues to decrease.
[0061] As described above, when 12-MG is coated on the Cu current collector, the overpotential decreases. As Figure 2 shown in part (a), after the voltage spike, the overpotential decreases significantly. This is due to the decrease in the charge transfer overpotential, the diffusion (in the SEI) overpotential, and / or the crystallization overpotential. The decrease in the charge transfer overpotential and the diffusion overpotential are estimated by Figure 3 the EIS measurement in. The decrease in crystallinity can be another reason for the reduction of the total overpotential by coating with 12-MG. The conversion reaction and / or the homogeneity of 12-MG, which are inherent properties of the amorphous metal alloy, can reduce the crystallization overpotential. First, after lithium diffuses into 12-MG and lithium deposition occurs, it is expected that 12-MG changes from lithium-phobic to lithium-philic coating. The transformation of 12-MG can obtain Figure 5Support for XPS. The Zr binding energy curve derived from the deposited 12-MG consists of the previously reported Zr binding energies from Zr-based amorphous metal alloys. After 0.5 cycles (lithium deposition), no Zr was detected on the lithium deposit, indicating that 12-MG acts as a seed layer. After 1.0 cycle (lithium desorption), the binding energy of Zr increased by 0.5 - 0.6 eV, indicating Zr oxidation. After 1.5 cycles (lithium deposition), the lithium deposit was removed and the binding energy of Zr was analyzed, and an increase of 0.5 - 0.6 eV was found, indicating that Zr had been oxidized. That is, as the number of deposition cycles on the current collector increases, it can be seen that 12-MG maintains an oxidized state compared to the 12-MG film before cycling. This is because the crystallization overpotential (η c ) prevents the inclusion of adsorbed atoms in the electrode. The adsorbed atoms located from the electrolyte to the electrode surface diffuse to the growth stage and finally reach stable growth positions (such as kinks). The Nernst equation can be used to estimate η c , which varies mainly according to the ratio of the concentration (or activity) of adsorbed atoms at the growth site and near the growth site. The higher η c is, the higher the concentration of adsorbed atoms in the surface region far from the growth position. This is interpreted as the diffusion rate of adsorbed atoms being slower compared to the reaction rate of adsorbed atoms on steps and kinks. If the surface diffusivity decreases, the surface diffusion penetration distance (λ 0 ) becomes shorter. The average current density (i) is a function of the overpotential, the distance between the growth points of two particles (2 x0 ), and λ 0 under normal state conditions.
[0062] (Equation 1)
[0063]
[0064] (Equation 2)
[0065]
[0066] Among them,
[0067]
[0068] In the above Equation 1 and Equation 2, i 0 , α, z, F, R, T, D, and c are the exchange current density, charge transfer coefficient, charge transfer atomic valence, Faraday constant, gas constant, temperature, surface diffusivity, and equilibrium concentration of adsorbed atoms (when η = 0), respectively. Since Figure 2 the overpotential in part (a) is measured at a constant current, it can be assumed that the overpotential is measured under normal state conditions. Equation 1 (λ 0 / x0 >> 1) represents no interference with the simple charge transfer current density, i.e., crystallization. In contrast, Equation 2 (λ 0 / x 0 << 1) represents the relationship between the current and the pure crystallization overpotential. In this case, if η is multiplied by the exponential term of λ 0 , the effective charge transfer coefficient of Equation 2 is reduced to half of Equation 1. According to Equation 1 and Equation 2, if the crystallization overpotential dominates, the importance of λ 0 / x 0 will increase in the equation. If λ 0 / x 0 increases, then under constant current conditions, η c of Equation 2 decreases. According to Equation 2, the growth overpotential of Zr-CC is lower than that of bare Cu in part (a) of Figure 2 , which means that the diffusivity of the adsorbed atoms on Zr-CC is high (the larger λ 0 ) and the distance between adjacent nuclei is shorter (the smaller x 0 ). Since a lower overpotential generates fewer nuclei, a smaller x 0 can be achieved by forming nuclei in the 2D shape. It is known that nuclei in the 2D shape are formed on the surface without defects such as potential and grain boundaries. At the initial stage of lithium deposition (see Figure 4 ), the flat and uniform Li layer on Zr-CC also supports the formation of nuclei in the 2D shape on Zr-CC. As λ 0 / x 0 increases, the current density also decreases because the adsorbed atoms are more evenly distributed. Therefore, Zr-MG coating helps to form nuclei in the 2D shape, increase the surface diffusivity, and prevent dendrite formation by reducing the local current density.
[0069] The reduction of the crystallization overpotential is due to the uniformity of the Zr-MG thin film, which can be clearly seen from Equation 2. This is supported by the result that "the crystallization of Zr-MG leads to a reduction in the Coulombic efficiency". In part (a) of Figure 5 , a half-cell was prepared using a current collector coated with a 12-nm-thick Zr MG, and at 1.0 mA / cm 2 and 1.0 mAh / cm 2Under the conditions of 0.5 cycles, 1.0 cycles, and 1.5 cycles respectively, the battery cells were disassembled. If necessary, the samples were rinsed with 1,2-dimethoxyethane (DME, Sigma Aldrich) to remove residual Li salts. Then, a total of 4 samples were analyzed by X-ray Photoelectron Spectroscopy (XPS), namely the 3 disassembled electrodes and the current collector coated with 12 nm thick Zr MG. In Figure 5 of (b) and Figure 5 of (c), half-cells were prepared using current collectors coated with 12 nm thick Zr MG, and after 1.0 cycle under the conditions of 1.0 mA / cm 2 and 1.0 mAh / cm 2 , the battery cells were disassembled. If necessary, the samples were rinsed with 1,2-dimethoxyethane (DME, Sigma Aldrich) to remove residual Li salts. Then, TEM was used to observe the images of a total of 2 samples at a magnification of 600,000, namely the 1.0-cycle electrode after disassembly and the current collector coated with 12 nm thick Zr MG. The amorphous structure of 12-MG was maintained during the lithium deposition / lithium desorption process, as shown in Figure 5 part (c) of Figure 5 and
[0070] confirmed by TEM analysis as shown in part (d) of Figure 6 . In 4 , full cells were prepared using 12 nm and 16 nm thick Zr MG with excellent performance in half-cells (a bare Cu half-cell was also prepared for comparison with bare Cu). In the full cells, LiFePO 2 with a capacity of 1 mAh / cm 3 )) was used as the positive electrode. Then, charge and discharge were carried out at a rate of 0.2C, and the voltage range was 3.0 - 3.8V.
[0071] In Figure 7 part (a) of Figure 7 part (b) ofFigure 7 In part (e) and Figure 7 in part (f), a full cell was fabricated using a current collector coated with 12 nm thick ZrMG and bare Cu, and after the first charge cycle at a rate of 0.2C, the cell was disassembled. If necessary, the sample was rinsed with 1,2 - dimethoxyethane (DME) to remove residual Li salts. Then, the surface / profile was observed by SEM at a magnification of 2000. In Figure 7 part (c), Figure 7 part (d), Figure 7 in part (g) and Figure 7 in part (h), a full cell was fabricated using a current collector coated with 12 nm thick ZrMG and bare Cu, and after the 100th charge cycle at a rate of 0.2C, the cell was disassembled. If necessary, the sample was rinsed with 1,2 - dimethoxyethane (DME) to remove residual Li salts. Then, the surface / profile was observed by SEM at a magnification of 2000. The 12 - MG coating on the current collector, as a cathode material, improved the cycling performance of the LiFePO 4 full cell. The first discharge capacity of the 15Ph5 full cell was 130.7 mAh g -1 . After 100 cycles, the capacity retention rate with an average Coulombic efficiency of 99.4% was 56.0%. Uniformly coating 12 - MG on the current collector is an innovative method to obtain excellent electrochemical performance for a non - negative lithium metal battery, because the amorphous structure of the non - negative lithium metal battery uniformly provides nucleation sites, and when absorbing lithium, the sites are further optimized. In addition, the conductivity of 12 - MG is beneficial to reducing the series impedance. It is well known that amorphous metal alloys have been reported to be used as active electrode materials in lithium - ion batteries, but the thin films of amorphous metal alloys have not been investigated as seed layers on current collectors. In contrast, for a full cell with bare Cu, the first discharge capacity was 106.0 mAh g -1 . After 100 cycles, the capacity retention rate was only about 47.3%, and the average Coulombic efficiency was in the range of 90% to 99%. The first discharge capacity of 12 - MG was about 23% higher than that of bare Cu. This demonstrates the advantages of 12 - MG as a seed layer. The upper end and cross - sectional shape of lithium after the first deposition (shown in Figure 7 ), compared with bare Cu where a higher first discharge capacity was confirmed in 12 - MG, shows more densely deposited Li in 12 - MG, and it can be seen from the cross - sectional image that even after 100 cycles, the thickness uniformity slightly decreases and dense lithium deposition is achieved. For bare Cu, discontinuous and non - uniform lithium deposition occurs.
[0072] [Preparation method of electrode (negative electrode)]
[0073] A lithium foil with a thickness of 200 μm was cut into a diameter of 16 mm to prepare the negative electrode.
[0074] [Cell Preparation Method]
[0075] During the preparation of the full cell, CR2032 coin cells were used, and the cell was prepared in a glove box under an Ar atmosphere (O 2 <1 ppm, H 2 O <1 ppm). The electrolyte used was 1,3-dioxolane (DOL) / 1,2-dimethoxyethane (DME) (1:1) containing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with 2 wt% lithium nitrate (LiNO 3 ). The positive electrode used was LiFePO with a capacity of 1.5 mAh / cm 2 of 4 (LFP: Super P: PVDF = 8:1:1). The full cell was prepared in the following order: outer shell, negative electrode (lithium metal with a diameter of 16 mm), separator (Celgard 2400), 70 μL of electrolyte, spacer, positive electrode (LFP with a diameter of 14 mm), gasket, wave spring, and lid.
[0076] [Cell Test Conditions]
[0077] The full cell test was carried out at a rate of 1.0 C and a voltage range of 3.0 V to 3.8 V.
[0078] Refer to Figure 8 In a lithium metal secondary battery including a positive electrode, a lithium metal negative electrode, an electrolyte, and a separator, at 1.5 mA / cm 2 , with the electrolyte being DOL / DME 1 M LiTFSl + 2 wt% LiNO 3 , in a full cell with a charge / discharge rate of 1.0 C, short circuit occurred during 179 cycles for bare lithium.
[0079] [Electrode (Negative Electrode) Preparation Method]
[0080] A lithium foil with a thickness of 200 μm was cut into a diameter of 16 mm to prepare a lithium disk. By magnetron sputtering, 12 nm of Zr-based metallic glass was deposited on the lithium disk to prepare the negative electrode. The sputtering was carried out under DC conditions of 125 W for 45 seconds and in an Ar (99.999%) sputtering environment of 5 x 10 -5 Torr.
[0081] [Method for preparing battery cell]
[0082] During the preparation of the full cell, CR2032 coin cells were used, and the battery cells were prepared in a glove box under an Ar atmosphere (O 2 <1 ppm, H 2 O <1 ppm). The electrolyte used was 1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME) with a ratio of 1:1 containing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 2 wt% lithium nitrate (LiNO 3 ). The positive electrode used was LiFePO 2 with a capacity of 1.5 mAh / cm 4 (LFP:Super P:PVDF = 8:1:1). The full cell was prepared in the following order: outer shell, negative electrode (Zr-based MG / Li with a diameter of 16 mm), separator (Celgard 2400), 70 μL of electrolyte, spacer, positive electrode (LFP with a diameter of 14 mm), gasket, wave spring, and lid.
[0083] [Battery cell test conditions]
[0084] The full cell test was carried out at a rate of 1.0 C and a voltage range of 3.0 V to 3.8 V.
[0085] Referring to Figure 9 part (a) and Figure 9 part (b), in a lithium metal secondary battery, at 1.5 mA / cm 2 , with the electrolyte being DOL / DME 1M LiTFSl + 2wt% LiNO 3 , and the charge / discharge rate being 1.0 C for the full cell, it can be seen that for the negative electrode coated with Zr-based amorphous metal alloy, the initial capacity is larger than that of bare lithium and the interval capacity is kept constant and large.
[0086] [Method for preparing electrode (negative electrode)]
[0087] A lithium disk was prepared by cutting a lithium foil with a thickness of 200 μm into a diameter of 16 mm. A negative electrode was prepared by magnetron sputtering 5 nm of Ti-based metallic glass on the lithium disk. The sputtering was carried out under DC conditions of 125 W for 45 seconds and in an Ar (99.999%) sputtering environment of 5x10 - 5 Torr.
[0088] [Method for preparing battery cell]
[0089] During the preparation of the full cell, CR2032 coin cells were used, and the battery cells were prepared in a glove box under an Ar atmosphere (O 2 <1 ppm, H 2 O < 1 ppm). The electrolyte used was 1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME) with a ratio of 1:1 containing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 2 wt% lithium nitrate (LiNO 3 ). The positive electrode used was LiFePO 2 with a capacity of 1.5 mAh / cm 4 (LFP:Super P:PVDF = 8:1:1). The full cell was prepared in the following order: outer shell, negative electrode (Ti-based MG / Li with a diameter of 16 mm), separator (Celgard 2400), 70 μL of electrolyte, spacer, positive electrode (LFP with a diameter of 14 mm), gasket, wave spring, and lid.
[0090] Referring to Figure 10 part (a) and Figure 10 part (b), in a lithium metal secondary battery, at 1.5 mA / cm 2 , with the electrolyte being DOL / DME, 1 M LiTFSl + 2 wt% LiNO 3 , and the charge / discharge rate being 1.0 C in a full cell, it can be seen that for the negative electrode coated with the Ti-based amorphous metal alloy, the initial capacity is larger than that of bare lithium and the interval capacity is kept constant and large.
[0091] The present invention is not limited to the described embodiments, but can be prepared in many different forms, and those of ordinary skill in the technical field to which the present invention pertains should understand that the present invention can be implemented in other specific forms without changing the technical idea or required features of the present invention. Therefore, it should be understood that the above-described embodiments are exemplary in all aspects and not restrictive.
Claims
1. An anode-free lithium secondary battery with an amorphous metal alloy coating, characterized in that, the anode-free lithium secondary battery includes: a positive electrode; a current collector, facing the positive electrode and made of copper foil, an electrolyte located between the positive electrode and the current collector, and a separator separating the positive electrode and the current collector; an amorphous metal alloy is coated on the interface where the current collector contacts the electrolyte.
2. The anode-free lithium secondary battery with an amorphous metal alloy coating according to claim 1, characterized in that, the amorphous metal alloy is a Zr-based amorphous metal alloy.
3. The anode-free lithium secondary battery with an amorphous metal alloy coating according to claim 2, characterized in that, The Zr-based amorphous metal alloy is Zr x Cu y Ni z Al w compound wherein, the range of x is 35 to 70, the range of y is 20 to 50, the range of z is 7 to 15, and the range of w is 3 to 5.
4. The anode-free lithium secondary battery with an amorphous metal alloy coating according to claim 1, characterized in that, the amorphous metal alloy is a Ti-based amorphous metal alloy.
5. The anode-free lithium secondary battery with an amorphous metal alloy coating according to claim 4, characterized in that, The Ti-based amorphous metal alloy is Ti a Zr b Si c compound wherein, the range of a is 45 to 85, the range of b is 20 to 50, and the range of c is 5 to 10.
6. The anode-free lithium secondary battery with an amorphous metal alloy coating according to claim 1, characterized in that, the coating thickness of the amorphous metal alloy is 8 nm to 500 nm.
7. A lithium metal secondary battery with an amorphous metal alloy coating, characterized in that, including: a positive electrode, a lithium metal negative electrode arranged opposite to the positive electrode, an electrolyte located between the positive electrode and the lithium metal negative electrode, and a separator separating the positive electrode and the lithium metal negative electrode; an amorphous metal alloy is coated on the surface of the lithium metal negative electrode.
8. A lithium secondary battery with an amorphous metal alloy coating, characterized in that, including: a positive electrode, a lithium metal negative electrode arranged opposite to the positive electrode, a current collector in contact with the lithium metal negative electrode and located in the opposite direction to the positive electrode and made of copper foil, an electrolyte located between the positive electrode and the lithium metal negative electrode, and a separator separating the positive electrode and the lithium metal negative electrode; an amorphous metal alloy is coated on the surface of the lithium metal negative electrode.
9. A all-solid-state secondary battery with an amorphous metal alloy coating, characterized in that, including: a positive electrode, a negative electrode arranged opposite to the positive electrode, and a solid electrolyte filled between the positive electrode and the negative electrode; an amorphous metal alloy layer exists on the interface between the solid electrolyte and the negative electrode.
10. A negative electrode current collector, characterized in that, an amorphous metal alloy is coated on the surface.